2023
DOI: 10.1039/d2qo02019j
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free visible-light-induced decarbonylative C–H alkylation of quinoxalin-2(1H)-ones

Abstract: Direct functionalization of C(sp3)–H bonds is an effective, straightforward method for accessing a diverse array of heteroarene derivatives. However, its wide application is limited by the need for to use...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 43 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Conducting the semiheterogeneous hydroxylation with other semiconductor photocatalysts, including g-C 3 N 4 , TiO 2 , CdS, CdSe, and ZnO, gave lower efficiencies (entry 2). Without any photocatalyst, the template reaction gave 2a in 28% yield (entry 3), presumably due to the fact that 1a can absorb ultraviolet–visible light and act as a photosensitizer (entry 3) . Exchanging NPh 3 with a different redox mediator diminished the reaction yield, delivering product 2a in 69–79% yields when NHPI, Cp 2 Fe, or DIPEA was used (entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…Conducting the semiheterogeneous hydroxylation with other semiconductor photocatalysts, including g-C 3 N 4 , TiO 2 , CdS, CdSe, and ZnO, gave lower efficiencies (entry 2). Without any photocatalyst, the template reaction gave 2a in 28% yield (entry 3), presumably due to the fact that 1a can absorb ultraviolet–visible light and act as a photosensitizer (entry 3) . Exchanging NPh 3 with a different redox mediator diminished the reaction yield, delivering product 2a in 69–79% yields when NHPI, Cp 2 Fe, or DIPEA was used (entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…Speaking of energy transfer processes in the context of the present work, the excited photosensitizers are known to transfer its energy to ground‐state molecular oxygen ( 3 O 2 ) to generate singlet oxygen ( 1 O 2 ), to attain selective chemical transformations [71–73] . Also, literature precedents suggested that quinoxalin‐2(1 H )‐ones could assist energy transfer to ground‐state molecular oxygen ( 3 O 2 ) to generate a singlet oxygen ( 1 O 2 ), to accomplish the chemical conversions [19,74–76] . So, we harped upon an observation that singlet oxygen ( 1 O 2 ), could help in the generation of alkyl radical via a hydrogen‐atom‐transfer ( HAT ) process, which upon coupling with quinoxalin‐2(1 H )‐ones, would be converted to 3‐functionalized quinoxalin‐2(1 H )‐ones.…”
Section: Introductionmentioning
confidence: 95%
“…[71][72][73] Also, literature precedents suggested that quinoxalin-2(1H)-ones could assist energy transfer to ground-state molecular oxygen ( 3 O 2 ) to generate a singlet oxygen ( 1 O 2 ), to accomplish the chemical conversions. [19,[74][75][76] So, we harped upon an observation that singlet oxygen ( 1 O 2 ), could help in the generation of alkyl radical via a hydrogen-atomtransfer (HAT) process, which upon coupling with quinoxalin-2(1H)-ones, would be converted to 3functionalized quinoxalin-2(1H)-ones. Corroborating the above hypothesis, we have developed an efficient, catalyst-and oxidant-free protocol to construct C-3 alkylated quinoxalin-2(1H)-ones using visible light.…”
Section: Introductionmentioning
confidence: 99%
“…9 reported a visible-light-induced decarbonylative C−H alkylation of quinoxalin-2(1H)-ones using alkyl aldehydes as alkyl radical precursors. 10 ■…”
Section: ■ Introductionmentioning
confidence: 99%
“…Herein, we report a visible-light-induced photocatalyst-free strategy for selective C3–H aroylation of quinoxalin-2­(1 H )-ones by employing arylaldehydes as acyl radical precursors with air as the sole oxidant (Scheme D). During the course of our research, Wang and co-workers reported a visible-light-induced decarbonylative C–H alkylation of quinoxalin-2­(1 H )-ones using alkyl aldehydes as alkyl radical precursors …”
Section: Introductionmentioning
confidence: 99%